Student’s Willingness to Communicate in English in EFL Digital Context: A Narrative Inquiry - Lutfi Ro’ihatul Jannah; Fitri Awaliyatush Sholihah; Dzurriyyatun Ni’mah (Journey: Journal of English Language and Pedagogy, 2024)
This study investigates the impact of social media on students' Willingness to Communicate (WTC) in digital contexts in English as a Foreign Language (EFL). WTC is defined as an individual's readiness to communicate verbally or remain silent when given the freedom to choose. This research utilizes a Narrative Inquiry approach to explore the experiences of an Indonesian EFL learner at the University of Islam Malang. Data was collected through in-depth narrative interviews, focusing on the participant's use of social media platforms such as Facebook, YouTube, Instagram, Twitter, TikTok, and Telegram for English communication. Findings reveal that digital interactions significantly enhance the participant's motivation, confidence, and language proficiency. Social media platforms facilitate real-time communication, expose learners to diverse linguistic contexts, and provide opportunities for immersive language practice. This study underscores the importance of integrating digital tools into traditional language education to support self-directed learning and improve students' WTC in English. These insights contribute to the growing research on Informal Digital Learning of English (IDLE) and its role in language acquisition and communication readiness.